Power system loading margin enhancement by optimal STATCOM integration – A case study. (January 2020) - Sreedharan, Sasidharan; Joseph, Tibin; Joseph, Sebin; Chandran, Chittesh Veni; J, Vishnu; Das P, Vipin
Abstract: Safe and secure network operation with acceptable voltage level has become a challenging task for utilities requiring corrective measures to be implemented. Network upgrades using Flexible Alternating Current Transmission System devices are being considered to serve this purpose. To this end, static loading margin enhancement by optimal static synchronous compensator (STATCOM) allocation to enhance the power transfer capability with minimal voltage variation is presented. Maximum loadability is formulated as an optimization problem, subjected to voltage and small-signal stability constraints. Stability indices are presented and incorporated with the optimization problem to ensure secure operation under maximum loading. The scheme is executed with the IEEE system and an Indian utility network. Improved voltage regulation with different loading condition was achieved for both test networks, with the service rendered by the optimally placed STATCOM. Moreover, it facilitates an additional 50% capacity release in both test systems for hosting the active power and loads.